Treatment and Rehabilitation of Abused and Neglected Children an Inpatient Center Model - Sunay Fırat; Necmi Çekin; Mete Korkut Gülmen; Ayşe Avcı (Adli Tıp Bülteni, 2014)
Rehabilitation and treatment centers are organizations that provide services for children and adolescents, with the main goal being to implement a “mental health” treatment plan for the individuals under their care. These organizations, which provide a continuous 24-hour service, may differ from one another in terms of the specific programs and treatment methods they apply.